PERHITUNGAN HARGA POKOK PRODUKSI (HPP) DENGAN MENGGUNAKAN METODE FULL COSTING (STUDI KASUS PADA UD. SAMBAL PECEL FAHMI, KOTA PARE) - Yudhantika, Aulia (Jurnal Ilmiah Mahasiswa FEB, 2017)
In this global era, companies are required to increase their efficiency and effectiveness in their production process in order to increase their competitiveness. Today, companies requires to have accuracy in calculating their production cost. UD. Fahmi , a company producing and selling sambal pecel, has not calculated their cost of goods manufactured based on the accounting standards. The failure has created inaccuracy in the determination of cost of goods manufactured, causing the selling price either too high or too low. This descriptive research is a case study that uses quantitative data, where the sources are secondary data. Collected from interviews and documentation, the data were analyzed using quantitative descriptive analysis. Based on the observation, it is evident that there is a  gap in UD.  Fahmi  because  the  business has  not calculated their  cost of goods manufactured correctly, so they fail to identify and group their costs accurately. Different results were derived from both calculations, i.e . full costing method and the company’s method. The cost of goods manufactured obtained from full costing method is lower than that obtained from the company’s method. This happens since full costing method is more detailed than the method used by the comp any.Keywords :  Cost Accounting, Cost of Goods Manufactured, Full Costing Method